Sanitary and hygienic conditions for effective sports activities of players - Kogan, O. S.; Yamileva, R. M.; Greb, A. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to give a detailed sanitary and hygienic description of the conditions of professional sports activities of team sports athletes and to prove that overload and overtraining of the body cannot but have a negative impact on the health of athletes, especially among athletes with high professional experience.